Catatan Persebaran Russula cf. cyanoxantha di Hutan Kampus Institut Pertanian Bogor - Putra, Ivan Permana; Haryadi, Silva Restiana; Nafsahan, Hury Khastina; Emillio, Guido Qais; Nuraeni, Siti Panesya; Anisyah, Fara Ayu; Khairani, Hafifatunil (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2023)
Russula cyanoxantha is one of a group of ectomycorrhizal-forming mushrooms. This species has a main distribution in the four seasons region. Until now, there is limited information on the distribution and taxonomic studies of this species of mushroom in Indonesia. Therefore, this study aimed to add information on the morphological characteristics, taxonomy, and distribution of R. cyanoxantha in Indonesia. This study was conducted in the campus forest of IPB University. Fresh fruiting bodies were observed in the field and in the laboratory. The parameters observed were macroscopic and microscopic characters of the collected samples. The mushroom found had cap colored in shades of white, gray, and purplish. The lamellae are white to cream colored and adnate to the cap, cylindrical stipe. Spores are round to oval with ornaments in the form of small spines on their cell walls. The results of this study are expected to contribute towards the addition of data on Russula mushrooms in Indonesia.